2016
DOI: 10.3168/jds.2016-11134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for extended-spectrum β-lactamase- and AmpC-producing Escherichia coli in dairy farms

Abstract: A cross-sectional study was conducted to evaluate the prevalence of extended-spectrum β-lactamase (ESBL)- and plasmid-mediated AmpC-producing Escherichia coli and associated risk factors in dairy herds. One hundred dairy herds were randomly selected and sampled to study the presence of ESBL- and AmpC-producing E. coli in slurry samples. The sensitivity of testing slurry samples for ESBL/AmpC herd status is less than 100%, especially for detecting herds with a low ESBL/AmpC prevalence. Therefore, whereas herds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 33 publications
7
94
4
1
Order By: Relevance
“…In multivariable regression models, CTX-M presence was negatively associated with high biosecurity (closed herds compared with un-quarantined open herds; OR 0.05, P = 0.004) and superior calf feeding equipment hygiene (65 U.K. herds, Snow et al, 2012). The presence of ESBL/AmpC correlated with treatment of all mastitis cases with antimicrobial drugs (OR 3.9, P = 0.02) and increasing proportion of calves treated with antimicrobials (86 Dutch herds, Gonggrijp et al, 2016). In the latter study, various features of biosecurity were not identified as risk factors, but much of the variation remained unexplained in the final model and follow-up testing 6 months later showed that many farms had changed status, possibly owing to issues with sensitivity of detection.…”
Section: Risk Factors For Amr In Commensal Bacteriamentioning
confidence: 99%
“…In multivariable regression models, CTX-M presence was negatively associated with high biosecurity (closed herds compared with un-quarantined open herds; OR 0.05, P = 0.004) and superior calf feeding equipment hygiene (65 U.K. herds, Snow et al, 2012). The presence of ESBL/AmpC correlated with treatment of all mastitis cases with antimicrobial drugs (OR 3.9, P = 0.02) and increasing proportion of calves treated with antimicrobials (86 Dutch herds, Gonggrijp et al, 2016). In the latter study, various features of biosecurity were not identified as risk factors, but much of the variation remained unexplained in the final model and follow-up testing 6 months later showed that many farms had changed status, possibly owing to issues with sensitivity of detection.…”
Section: Risk Factors For Amr In Commensal Bacteriamentioning
confidence: 99%
“…By contrast, in China, almost a quarter of E. coli isolates from bovine mastitis were ESBL‐producing coliforms (Ali et al., ). In the UK and the Netherlands, presence of ESBL‐coliforms has been linked to presence or use of 3/4GC in waste milk and slurry (Gonggrijp et al., ; Randall et al., ). Despite the low prevalence of ESBL‐producers among mastitis pathogens in Western countries, the association between 3/4GC use and ESBL prevalence on dairy farms together with WHO concerns about use of those compounds in animals will in all likelihood limit their availability as mastitis treatment products.…”
Section: Socio‐economic Impact and Zoonotic Aspectsmentioning
confidence: 99%
“…No other selection criteria were applied. To calculate the DDDA, we followed standard operating procedures of the Netherlands Veterinary Medicines Authority as described by Gonggrijp et al (2016).…”
Section: Antimicrobial Use Associated With Udder Healthmentioning
confidence: 99%